School Compensation Strategies and Staff Job Performance in Private Secondary Schools in Kwara State - Adeseko Sunday Olaifa; Mumin Agaka Ahmed; Afeez Adesina Shittu; Kingsley Chigozie Akpala; Ebunlomo Oreoluwa Olaifa (PAEDAGOGIA, 2025)
Compensation is a very significant tool for enhancing staff job performance. The study investigated the relationship between school compensation strategies and staff job performance in private secondary schools in Kwara State. The study examined the various compensation strategies available to private secondary school Staff in Kwara State. A descriptive survey of correlation type was used as a research design. Using research advisors, a proportional sampling technique was adopted to select 400 staff and 40 private secondary schools in Kwara State. 350 respondents comprised school teachers and administrators of private secondary schools in Kwara State. A descriptive survey research design was employed and an adapted questionnaire instrument titled School Compensation Strategies and Staff Job Performance Questionnaire (SCSSJP) was used to collect data from the respondents. The study's findings indicated that compensation strategies in private secondary schools in Kwara State were relatively high, staff job performance was moderate and a significant relationship existed between compensation strategies and staff job performance in these institutions. The research indicated that private secondary schools in Kwara State lack sufficient non-monetary compensation strategies, negatively impacting staff job performance. The study shows that staff job performance was affected by salary, incentives, fringe benefits and staff recognition. It was recommended that private secondary schools in Kwara State should develop and implement effective compensation strategies that include competitive salaries, incentives, merit-based pay, longevity pay and opportunities for staff professional development and growth